Approaches to the comparative method and analysis of the world-system: typologies to understand the rural impact of the neoliberal expansion, Chile (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This article is a theoretical-methodological reflection on the potentialities of the link between the comparative method and anthropology, expressed in the world-system analysis. From this mixture, we propose, from our ethnographic experience, a typology to understand the impact of the expansion of capitalism in its neoliberal phase on rural settlements in Chile. We present the possibility of using the comparative method to understand them simultaneously as constituent entities of this system. Thus, we assume for reflection that these groups participate in an interconnected way in a historical system based on globally integrated capitalist appropriation and accumulation, which favors the configuration of contemporary conflicts of different origins and characteristics, the study of which is of utmost importance for knowledge of these populations.
Keywords: Comparative method; neoliberalism; capitalism; ethnography; rural groups